Architectural and sculptural remains of the original Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
Several architectural and sculptural remains, which must have been part of the original Chaunsath Yogini Temple, are scattered nearby. A large portion of these remains is comprised of the ghantasamvarna shikhara (bell-roofed superstructure) that would have been part of the mandapa (pillared hall) shikhara.